A new portable toluidine blue/aptamer complex-on-polyethyleneimine-coated gold nanoparticles-based sensor for label-free electrochemical detection of alpha-fetoprotein - Yaiwong, Patrawadee; Anuthum, Siriporn; Sangthong, Padchanee; Jakmunee, Jaroon; Bamrungsap, Suwussa; Ounnunkad, Kontad (Frontiers in Bioengineering and Biotechnology, 2023)
The quantification of alpha-fetoprotein (AFP) as a potential liver cancer biomarker which is generally found in ultratrace level is of significance in biomedical diagnostics. Therefore, it is challenging to find a strategy to fabricate a highly sensitive electrochemical device towards AFP detection through electrode modification for signal generation and amplification. This work shows the construction of a simple, reliable, highly sensitive, and label-free aptasensor based on polyethyleneimine-coated gold nanoparticles (PEI-AuNPs). A disposable ItalSens screen-printed electrode (SPE) is employed for the fabrication of the sensor by successive modification of PEI-AuNPs, aptamer, bovine serum albumin (BSA), and toluidine blue (TB), respectively. The AFP assay is easily performed when the electrode is inserted into a small Sensit/Smart potentiostat connected to a smartphone. The readout signal of the aptasensor derives from the electrochemical response of TB intercalating into the aptamer-modified electrode after binding with the target. The reduced current response of the proposed sensor is proportional to the AFP concentration due to the restriction of the electron transfer pathway of TB by a number of insulating AFP/aptamer complexes on the electrode surface. PEI-AuNPs improve SPCE’s reactivity and provide a large surface area for aptamer immobilization whereas aptamer provides selectivity to the target AFP. Consequently, this electrochemical biosensor is highly sensitive and selective for AFP analysis. The developed assay reveals a linear range of detection from 10 – 50000 pg mL1 with R2 = 0.9977 and provided a limit of detection (LOD) of 9.48 pg mL1 in human serum. With its simplicity and robustness, it is anticipated that this electrochemical-based aptasensor will be benefit for clinical diagnosis of liver cancer and further developed for other biomarkers analysis.